The Sustainability of MSME Business Competitiveness in Bogor City in Review from Entrepreneurial Orientation, Financial Capital and Innovation - Muhammad Akbar; Marwan Effendi; Winanto Nawarcono; Aji Priambodo; Sufyati H.S. (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2023)
Micro, small, and medium enterprises (MSMEs) play a crucial role in driving economic growth and job creation in many countries, including Indonesia. However, MSMEs often face challenges in maintaining their long- term competitiveness. This research aims to examine the sustainability of MSME competitiveness in Bogor City, Indonesia, from the perspectives of entrepreneurial orientation, financial capital, and innovation. A total of 384 MSME owners/managers participated in this study. The research findings indicate that entrepreneurial orientation, financial capital, and innovation have a positive and significant correlation with MSME competitiveness. Furthermore, regression analysis reveals that entrepreneurial orientation, financial capital, and innovation significantly predict MSME competitiveness in Bogor City. These findings suggest that policymakers and stakeholders should focus on enhancing the entrepreneurial orientation of MSMEs, improving their access to financial resources, and fostering innovation capabilities to drive the sustainability of MSME competitiveness in Bogor City.